PRITHVI MAHABHUTA DOMINANT CHARACTERS IN PUGAPHALA (ARECA CATECHU LINN.) SCIENTIFICALLY ASSESSED THROUGH PHARMACOGNOSY AND PHARMACEUTICAL CHEMISTRY - Moond, Kamla; Vyas, Hitesh; R., Harisha C.; Shukla, V. J. (International Journal of Current Pharmaceutical Research, 2018)
Objective: The Areca catechu L. is a tropical fruit, which is also called betel nut and is widely distributed in different parts of the world. Areca catechu L is used for various treatment aliments in the form of various preparations especially in powdered form and it used extensively in Ayurveda to treat Mukhavikara, Aruchi, Yonishaithilya, Shvetapradara etc. Areca nut is commonly used as betel nut or supari, as it is often chewed wrapped in betel leaves (Paan). The aim is to assessment of Mahabhautika dominance in Pugaphala by pharmacognostical and pharmaceutical study. Methods: Microscopic, macroscopic study and phsico-chemical analysis of Pugaphala Churna. Results: In present study Pugaphala was selected as a Parthiva dominant drug according to its Rasa Panchaka, after that its Mahabhautika dominancy was assessed by pharmacognostical and pharmaceutical study and results also support that in Pharmaceutical study loss on drying is 4.4%w/w, in Pharmacognostical study Rhomboidal crystal, Lignified scleroid etc. were found these characters also showed that Pugaphala is having dominancy of Prithvi Mahabhuta. Conclusion: Prithvi dominancy in Pugaphala is scientifically assessed by Pharmacognostical and Pharmaceutical study.